Optimalisasi Peran Komando Operasi Khusus TNI Guna Menanggulangi Ancaman Terorisme dalam Rangka Operasi Militer Selain Perang (OMSP) - Mulyadi Mulyadi; Rudy Sumantri; Muh. Ilham M. Tr. Hanla (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to assess the role of the Indonesian National Military's Special Operations Command (Koopssus TNI) in combating terrorism within the framework of Military Operations Other Than War (OMSP). Given the growing complexity of transnational terrorism, this study identifies operational, legal, and institutional challenges faced by Koopssus TNI, evaluates inter-agency coordination, and discusses strategies for optimizing its effectiveness. Using qualitative methods, including interviews with military personnel and analysis of relevant legal frameworks, the study provides practical recommendations for strengthening the command's capabilities in counter-terrorism operations.